2015
DOI: 10.1371/journal.pone.0133702
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Rituximab in Refractory Inflammatory Myopathies Associated with Anti- Synthetase Auto-Antibodies: An Open-Label, Phase II Trial

Abstract: ObjectiveAnti-synthetase syndrome (anti-SS) is frequently associated with myositis and interstitial lung disease (ILD). We evaluated prospectively, in a multicenter, open-label, phase II study, the efficacy of rituximab on muscle and lung outcomes.MethodsPatients were enrolled if they were refractory to conventional treatments (prednisone and at least 2 immunosuppressants). They received 1 g of rituximab at D0, D15, and M6. The primary endpoint was muscular improvement based on manual muscular testing (MMT10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 24 publications
5
65
1
3
Order By: Relevance
“…7 In a recent study, not only did rituximab show improvement in pulmonary function but also led to a decrease in total creatine kinase levels, decreased steroid dosage, and decreased usage of immunosuppressive medications. 10 Interestingly, pulmonary function improvement may also be due to muscular strength reinforcement rather than just improvement of ILD itself. 10 During treatment, adverse effects of rituximab were mainly limited to infections, but not severe enough to require hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 In a recent study, not only did rituximab show improvement in pulmonary function but also led to a decrease in total creatine kinase levels, decreased steroid dosage, and decreased usage of immunosuppressive medications. 10 Interestingly, pulmonary function improvement may also be due to muscular strength reinforcement rather than just improvement of ILD itself. 10 During treatment, adverse effects of rituximab were mainly limited to infections, but not severe enough to require hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…10 Interestingly, pulmonary function improvement may also be due to muscular strength reinforcement rather than just improvement of ILD itself. 10 During treatment, adverse effects of rituximab were mainly limited to infections, but not severe enough to require hospitalization. 10 Early diagnosis of antisynthetase syndrome along with prompt initiation of the correct treatment regimen is critical to preventing disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter phase II study evaluated the efficacy of rituximab in individuals with SAM with anti-synthetase autoantibodies refractory to conventional treatment (GC and at least two immunosuppressive drugs) demonstrated that the majority of these patients had an increase in the Manual Muscle Testing (MMT)-8 followed by a reduction of CK levels and a reduction in the dose of GC (B) [87].…”
Section: How Long Should Sam Patients Receive Immunosuppressive / Immmentioning
confidence: 99%
“…At present, patients with different idiopathic inflammatory myopathies are treated with roughly the same medications. However, in the era when biological (molecular targeted) therapy is becoming a realistic option, it will be reasonable to consider therapeutic strategies separately for distinct subsets . In this context, the diagnostic criteria of myositis, which were formulated by Bohan and Peter in 1975, and are often still used now, do not seem appropriate for the current situation .…”
Section: Introductionmentioning
confidence: 99%